Peran Teknologi Informasi Dalam Peningkatan Daya Saing Destinasi Pariwisata Di Indonesia - Atmaja, Jerri Pria (Program Studi Pariwisata Program Sarjana, Fakultas Pariwisata, Universitas Udayana, 2023)
In the face of tourism competitiveness in Indonesia today. The development of digitalization-based information technology is very influential in helping to improve the personal branding of tourism destinations, thereby making changes to consumer perceptions of the tourism to be headed. This study aims to determine the effect of information technology on increasing tourism competitiveness in Indonesia. This research was carried out using descriptive qualitative methods. By collecting data using interview techniques and supported by other literary media. It can be seen from the results of the research that the existence of digital-based information technology has a major influence on the development of tourism competitiveness in Indonesia, especially increasing tourist interest visits to destinations in Indonesia. The existence of this information technology is also very influential on other industry players to get a good value chain from consumers, so information technology is very useful in all aspects of business that are oriented towards increasing effectiveness. Keywords: Daya Saing, Destinasi, Pariwisata, Teknologi Informasi